2015
DOI: 10.1007/s00701-015-2640-0
|View full text |Cite
|
Sign up to set email alerts
|

Anterior temporal lobectomy

Abstract: Knowledge of the temporomesial anatomy, including neurovascular structures around the brainstem, is essential to keep this procedure safe and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
0
21
0
3
Order By: Relevance
“…This wound was copiously irrigated and closed. The anterior temporal lobectomy was then performed as described [39]. Briefly, a temporal craniotomy is performed flush with the middle fossa.…”
Section: B Removal Of the Neuropace Device And Anterior Temporal Lobmentioning
confidence: 99%
“…This wound was copiously irrigated and closed. The anterior temporal lobectomy was then performed as described [39]. Briefly, a temporal craniotomy is performed flush with the middle fossa.…”
Section: B Removal Of the Neuropace Device And Anterior Temporal Lobmentioning
confidence: 99%
“…These patients were diagnosed as focal unilateral TLE by a comprehensive preoperative assessment, including seizure history and semiology, neurological examination, 3-Tesla magnetic resonance imaging (MRI), scalp electroencephalography, invasive electroencephalography. All patients were from Xuanwu hospital in Beijing and underwent anterior temporal lobectomy including hippocampus (Schaller and Cabrilo, 2016 ). The results of at least 1 year follow-up indicated that these patients achieved seizure free status (Engel class IA).…”
Section: Resultsmentioning
confidence: 99%
“…According to all of these examination results, the preoperative assessment conclusion was given by Beijing epilepsy center expert group members. Then, all of those patients also underwent anterior temporal lobectomy [ 37 ] for focal epilepsy at Xuan Wu Hospital Capital Medical University (XWHCMU) between January 2013 and January 2016, which included at least one year of postoperative follow-up. The follow-up results showed that all of those patients were free of disabling seizures (Engel class IA) after surgery.…”
Section: Resultsmentioning
confidence: 99%